2014
DOI: 10.1183/09031936.00095214
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated respiratory infection following lung transplantation

Abstract: The medical records of 170 adult patients who underwent lung transplantation between January 2010 and December 2012 were reviewed to assess the incidence, causative organisms, risk factors and outcomes of post-operative pneumonia and tracheobronchitis. 20 (12%) patients suffered 24 episodes of ventilator-associated pneumonia. The condition was associated with mean increases of 43 days in mechanical ventilation and of 35 days in hospital stay, and significantly higher hospital mortality (OR 9.0, 95% CI 3.2-25.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 39 publications
2
33
1
Order By: Relevance
“…A particular challenge is the development of pneumonia in the postoperative period of lung transplantation because its presentation may overlap with acute rejection that requires the opposite therapeutic approach (increase versus decrease of immunosuppressors). Recently, Riera and colleagues [2] reported that pneumonia was related to increased in-hospital death (42.9 vs 11.5 %; p = 0.01), while tracheobronchitis was not related to increased mortality (14.0 vs 14.7 %; p = 0.9) but both prolonged the duration of MV by more than 1 week. Interestingly, tracheobronchitis doubled episodes of pneumonia in this subset of patients.…”
Section: Diagnosis Of Pneumonia or Tracheobronchitismentioning
confidence: 99%
“…A particular challenge is the development of pneumonia in the postoperative period of lung transplantation because its presentation may overlap with acute rejection that requires the opposite therapeutic approach (increase versus decrease of immunosuppressors). Recently, Riera and colleagues [2] reported that pneumonia was related to increased in-hospital death (42.9 vs 11.5 %; p = 0.01), while tracheobronchitis was not related to increased mortality (14.0 vs 14.7 %; p = 0.9) but both prolonged the duration of MV by more than 1 week. Interestingly, tracheobronchitis doubled episodes of pneumonia in this subset of patients.…”
Section: Diagnosis Of Pneumonia or Tracheobronchitismentioning
confidence: 99%
“…Compared to other solid organ transplantations, lung transplantation (LT) is characterized by a higher complication rate and a lower survival rate . Respiratory tract infections are among the most prevalent early post‐LT complications, accounting for significant morbidity and mortality .…”
mentioning
confidence: 99%
“…8 With the exception of the studies from Al-Hasan and colleagues, 6 Azap and colleagues, 13 and Riera and colleagues, 9 the incidence of ESBL production in enteric pathogens was at least 40%. [6][7][8][9]11,12,14,21,23,25 Two other studies reported the proportion of enteric bacilli that were MDR (14.5% and 54.8%, respectively), but did not specify if these were ESBL producing or not. 26,28 One other study looked at the number of patients who were colonized with ESBL producing pathogens before liver transplantation.…”
Section: Prevalence Of Pathogens In Solid Organ Transplantmentioning
confidence: 92%
“…Data for methicillin-resistant Staphylococcus aureus (MRSA) were limited, with only 4 studies reviewed reporting on MRSA. [7][8][9][10] The prevalence of MRSA had wide variability being as low as 18% 9 and as high as 80%. 10 Few of these studies looked at Enterococcus spp.…”
Section: Introductionmentioning
confidence: 99%